Comprehensiveness, readability, and reliability of Brazilian websites available for lay people's guidance on adenotonsillectomy - Piña, Sofia Prata [UNESP]; Corrêa, Camila de Castro [UNESP]; Carvalho, Lídia Raquel de [UNESP]; Weber, Silke Anna Theresa [UNESP] (Elsevier, 2019)
Introduction: Adenotonsillectomy is an invasive surgical procedure, which may encourage the search for information by the lay population through online search engines. The quality of this information, however, requires an evaluation due to the wide diversity of the available content. Objective: To evaluate the quality, in terms of ethical principles, readability and comprehensiveness, of the most accessed websites concerning guidance to parents/guardians related to their children's recommended adenotonsillectomy. Methods: The websites mentioned on the first 10 pages obtained after the search using “removal”, “tonsils” and “adenoids” as keywords, after applying the inclusion and exclusion criteria, were selected. All were assessed using the Flesch Readability Index and Health on the Net Code tools, in addition to an evaluation of the content by two independent evaluators. The data were described, and the inter-rater agreement was calculated by the Kappa coefficient. Results: 34 websites were found, of the 100 assessed ones, which met the inclusion and exclusion criteria using the Google and Yahoo! Tools. Sixteen (47%) pages were considered reasonably difficult/difficult to read according to the Flesch Readability Index. Most of them met less than half of the analyzed ethical requirements according to the Health on the Net Code, and the overall comprehensiveness average was considered insufficient. Conclusion: A deficit of overall quality (comprehensiveness, readability, and ethical principles) was demonstrated for the websites available to parents or guardians about the adenotonsillectomy procedure in children.
Abrangência, legibilidade e confiabilidade de websites brasileiros para orientação da população leiga sobre adenotonsilectomia
Keywords: Communication barriers; Ethics; Internet; Tonsillectomy